Recent Updates on Jellyfish: Applications in Agro-based Biotechnology and Pharmaceutical Interests - Barzkar, Noora; Thumthanaruk, Benjawan; Kalhoro, Muhammad Saleem; Rungsardthong, Vilai; Phusantisampan, Theerawut (Applied Science and Engineering Progress, 2024)
Jellyfish are gelatinous sea creatures that belong to the subphylum Medusozoa of the phylum Cnidaria and are found on many beaches worldwide. Despite being considered a nuisance, jellyfish have many uses, such as being a source of high-value molecules such as collagen, gelatin, and protein hydrolysates and a source of high-protein food. Studies related to its availability, post-harvest applications, and need-based use in biomedicine are thrust research of analysis or investigation. Therefore, this review has been designed with all the latest information with a focus on applications of jellyfish in agro-based biotechnology and pharmaceutics. The review has been systematically arranged to present on the broader search platform for future research studies and possible need-based applications.